“Membentuk Jati Diri Akuntan” Melalui Nilai Keagamaan - Fadli Fendi Malawat; Muh Kashai Ramdhani Pelupessy (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to shape the identity of accountants through religious values of holiness. Tazkiyah is a method used to explore religious values in order to reposition the accountant's identity. The results of this study indicate that accounting has always had an image of holiness based on religious teachings. Meanwhile, the results of this study have implications for the ethical code of the accounting profession as an identity and as the basis for business practices, which cannot be separated from religious values. Furthermore, the results of this study also provide a solution to the perspective of Hebert Marcuse, who considers modern humans to be one-dimensional men.